P0377THE RELATIONSHIP BETWEEN SEVERITY OF INTERSTITIAL FIBROSIS AND ANEMIA IN PATIENT WITH PRIMARY GLOMERULONEPHRITIS: THE DATA FROM TSN-GOLD WORKING GROUP. (6th June 2020) - Cebeci, Egemen; Turgutalp, Kenan; Ozturk, Savas; Ozluk, Yasemin; Bek, Sibel Gokcay; Sumnu, Abdullah; Seyahi, Nurhan; Yavuz, Mahmut; Piskinpasa, Serhan Vahit; Akcay, Omer Faruk; Sakaci, Tamer; SAHIN, Garip; et al.
Abstract: Background and Aims: Anemia is one of the most important complications in chronic renal disease and inadequate erythropoietin production is the most important reason for anemia. Fibrosis of renal interstitium may be associated with inadequate synthesis of erythropoietin and anemia. In our study, we investigated the relationship between the severity of interstitial fibrosis (IF) in patients with primary glomerulonephritis (PGN) and anemia parameters. Method: A total of 2794 patients who were recorded to the database of the Turkish Society of Nephrology, Glomerular Diseases (TSN-GOLD) Working Group between May 2009 and June 2019 were included in our national multicenter (44 centers) study. Patients aged 16 years or more with documented biopsy were included in the study. Patients were divided into four groups according to IF severity. IF was not detected in the interstitial area, was defined as none, if fibrosis was present in less than 25% of the area, defined as mild, if fibrosis was present in 25-50%, defined as moderate and if more than 50%, defined as severe. Anemia was defined as hemoglobin <12 g/dl in adult female patients and <13 g/dl in adult male patients, according to Clinical Practice Guidelines for anemia of CKD published by The Kidney Disease: Improving Global Outcomes Foundation. The relationship between IF severity and anemia parameters at the time of biopsy was investigated. Results: In the study, 57% of the patients were male and their mean age was 41.0 ± 14.3 years. The mean eGFR was 82.7 ± 36.9 ml / min / 1.73 m 2 and the hemoglobin level was 13.1 ± 1.9 g/dl. General characteristics of patients with and without anemia are given in Table 1 . While 41.1% of patients had no IF, 41.2% had mild, 14.1% had moderate and 3.5% had severe IF. When the patients were divided into four groups according to the severity of IF, the mean hemoglobin and hematocrit levels were significantly different between the groups (Figure 1 ). Anemia was present in 960 patients (34.4%) (Figure 2 ). Anemia rate was significantly higher in the patients with IF than patients without IF (36.8% vs 30.9%, p = 0.001). Anemia rate was %25.1 in patients with eGFH≥60 ml/min/1.73m2 and 56% in patients with eGFR<60 ml/min/1.73m 2 . Gender, serum albumin, eGFR, proteinuria, presence of diabetes, presence of nephrotic syndrome, and presence of IF were the independent variables in the regression analysis of hemoglobin-related factors (Table 2). Conclusion: Approximately one-third of PGN patients had anemia at the time of biopsy and the frequency of anemia increases in patients with IF. The presence of IF is an independent risk factor associated with the development of anemia in PGN. The elucidation of the etiopathogenesis of anemia in PGN patients may play an important role in the follow-up and treatment of patients. Studies on IF can play a critical role.